Carbonization of polymers of intrinsic microporosity to microporous heterocarbon: Capacitive pH measurements. (December 2017) - Hernandez, Naiara; Iniesta, Jesus; Leguey, Vicente Montiel; Armstrong, Robert; Taylor, Stuart H.; Madrid, Elena; Rong, Yuanyang; Castaing, Rémi; Malpass-Evans, Richard; Carta, Mariolino; McKeown, Neil B.; Marken, Frank
Graphical abstract: Highlights: Direct "one-step" conversion of the polymer of intrinsic microporosity PIM-EA-TB-H2 to a microporous heterocarbon for applications in electrochemistry. Slow hydration of microporous aided by protons and perchlorate to give "pH-switchable" capacitance response. Carbonization temperature during PIM carbonization appears to be linked to pore size and microporosity effects in the resulting heterocarbon. Abstract: A nitrogen-containing polymer of intrinsic microporosity (PIM-EA-TB-H2 ; nitrogen adsorption surface area 846 m 2  g −1 ) is vacuum carbonized at 700 °C and thereby directly without post-treatment converted into a microporous heterocarbon (cPIM; N2 adsorption surface area 425 m 2  g −1 ). Nitrogen functionalities in the polymer backbone are retained in the heterocarbon and appear responsible for unusual time-, electrolyte-, and pH-dependent properties. Electrochemical characterization suggests a high specific capacitance (typically 50 F g −1 ) but only after prolonged immersion in aqueous HClO4 . The time-dependent increase in capacitance during immersion is assigned to slow hydration and ingress of HClO4 into hydrophobic micropores (H2 SO4 or H3 PO4 are more hydrophilic and much less effective). Once hydrated, the microporous heterocarbon exhibits pH-dependent capacitance "switching" over a wide pH range and analytical applications as "capacitive" pH sensor are proposed.